Non-Persistence With Antiplatelet Medications Among Older Patients With Peripheral Arterial Disease - Wawruch, Martin; Murin, Jan; Tesar, Tomas; Paduchova, Martina; Petrova, Miriam; Celovska, Denisa; Havelkova, Beata; Trnka, Michal; Aarnio, Emma (Frontiers in Pharmacology, 2021)
Introduction: Antiplatelet therapy needs to be administered life-long in patients with peripheral arterial disease (PAD). Our study was aimed at a) the analysis of non-persistence with antiplatelet medication in older PAD patients and b) identification of patient- and medication-related characteristics associated with non-persistence. Methods: The study cohort included 9,178 patients aged ≥65 years treated with antiplatelet medications in whom PAD was newly diagnosed 01/2012-12/2012. Patients with a 6-month treatment gap without antiplatelet medication prescription were classified as non-persistent. Characteristics associated with non-persistence were identified using the Cox regression. Results: At the end of the 5-year follow-up, 3,032 (33.0%) patients were non-persistent. Age, history of ischemic stroke or myocardial infarction, clopidogrel or combination of aspirin with clopidogrel used at the index date, higher co-payment, general practitioner as index prescriber and higher overall number of medications were associated with persistence, whereas female sex, atrial fibrillation, anxiety disorders, bronchial asthma/chronic obstructive pulmonary disease, being a new antiplatelet medication user (therapy initiated in association with PAD diagnosis), and use of anticoagulants or antiarrhythmic agents were associated with non-persistence. Conclusion: In patients with an increased probability of non-persistence, an increased attention should be paid to improvement of persistence.